Ocena ubezpieczenia jako metody zarządzania ryzykiem w przedsiębiorstwie - Kwiecień, Ilona (The Estimation of The Insurance as a Method In Business Risk Management Process, 2008)
The insurance was perceived as a synonym of the risk management for ages. In consequence of the transformations in the 20lh century, it has changed its role and now it became only one of risk management methods. This method should and can he used on the basis of risk analysis. And all advantages and disadvantages should he considered. In the article, the author estimates the insurance using criteria which were established as most important for risk management's methods selecting. In turns the author describes criteria such us: effectiveness, cost, additional benefits, compulsion, availability.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 357-366